Obesity and Arterial Compliance Alterations - Seifalian, Alexander M.; Filippatos, Theodosios D.; Joshi, Jatin; Mikhailidis, Dimitri P. (Current Vascular Pharmacology, 2010)
Obesity is associated with increased cardiovascular disease (CVD) risk, especially when excess body fat is distributed preferentially within the abdominal region. Obese subjects usually have increased arterial stiffness compared with non-obese subjects of similar age. The factors associated with increased arterial stiffness in obesity include endothelial dysfunction (decreased nitric oxide bioavailability), impaired smooth muscle cell function, insulin resistance, as well as elevated cholesterol and C-peptide levels. Furthermore, visceral fat, the adipose tissue-related renin-angiotensinaldosterone system and hyperleptinaemia contribute to the obesity-associated impaired arterial compliance. Weight loss improves CVD risk factors and arterial compliance. Because increased arterial stiffness is a marker of CVD risk these findings support the concept that the presence of obesity has vascular implications.
Keywords: insulin